Sociocultural influences and teacher education programs - McInerney, Dennis M.; Etten, Shawn Van (Emerald Publishing Limited, 2003)
In this volume we describe exemplary programs in teacher education that attempt to address some of the issues alluded to above. Our authors address theoretical perspectives on the importance of teacher education for improving educational outcomes; the achievement gap between different groups and in particular the significant achievement gap between indigenous students and other minorities and mainstream groups, and how this might be overcome by better trained teachers; and how teachers learn to be effective teachers and are these skills of effective teaching broadly applicable across all educational environments?
Includes index.
Keywords: Teachers -- Training of.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books